SNRApp - Rafati, Nima (SciLifeLab Serve, 2026)
**SNRApp** is an interactive web app to calculate the Signal-to-Noise Ratio (SNR) from spatial omics data. The user will need to upload an `anndata` and set the top and bottom percentile.